Profile Of Nutrition Among 24-59 Months Children in A Rural Area of Bengal, India - Basu, Mausumi; Sarkar, Kumaresh Chandra; Roy, Biman; Das, Palash; Barua, Jayanta Kumar; Biswas, Sukanta (National Journal of Community Medicine, 2014)
Introduction: Globally, 162 million under-five children were suffering from stunting; 99 million from underweight and 51 million from wasting in 2012. The Government of India has introduced NewWHO 2006 Child Growth Standards in India for monitoring growth of children. This study wasconducted with the objective to assess the magnitude of under-nutrition among 24-59 months children in a rural area of West Bengal and some social factors influencing their nutritional status. Materials and methods: A community based cross sectional study was conducted among 360 children of 24 – 59 months in ten randomly selected villages of West Bengal in March 2013 using a predesigned pretested schedule. Results: The prevalence of underweight, stunting and wasting was 49.17%, 59.44% and 20.28% respectively. Boys suffered more than girls in all indicators. The prevalence of under-weight, stunting and wasting was significantly associated with age of the study population, literacy status of parents and socio economic status but not with sex. Conclusion: The problem of under-nutrition amongst under-five children needs to be addressed through comprehensive preventive, promotive, curative and social measures.